2005
DOI: 10.2106/jbjs.c.00591
|View full text |Cite
|
Sign up to set email alerts
|

Modular Fixed-Bearing Total Knee Arthroplasty with Retention of the Posterior Cruciate Ligament

Abstract: In this single-surgeon series, modular fixed-bearing posterior cruciate-retaining total knee arthroplasties had good clinical and radiographic results with excellent survivorship for up to fifteen years. These results are comparable with those in long-term studies of posterior stabilized implants and of prostheses with mobile-bearing and nonmodular tibial inserts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(96 citation statements)
references
References 22 publications
4
87
1
4
Order By: Relevance
“…Our review showed improvement in mean Knee Society clinical and functional scores that parallel the results reported in studies that have not separated patients on the basis of patient age [1,2,6,8,12,19,27,30]. Although physician-generated scores suggest improvement, reporting biases that appear to overlook negative patient experiences were identified during this review, including minimizing the impact of revision procedures for patellar resurfacing, polyethylene wear, instability, and stiffness (Table 1).…”
Section: Discussionsupporting
confidence: 68%
“…Our review showed improvement in mean Knee Society clinical and functional scores that parallel the results reported in studies that have not separated patients on the basis of patient age [1,2,6,8,12,19,27,30]. Although physician-generated scores suggest improvement, reporting biases that appear to overlook negative patient experiences were identified during this review, including minimizing the impact of revision procedures for patellar resurfacing, polyethylene wear, instability, and stiffness (Table 1).…”
Section: Discussionsupporting
confidence: 68%
“…The early infection rate of 1.4% (two cases) in our series is consistent with the overall literature data. The paper from Boston [6] reported no early or late infections in their cohort. Whether a single-versus multisurgeon setting might have had an influence on the early infection rate remains unclear.…”
Section: Discussionmentioning
confidence: 89%
“…However, the definition of failure of TKA has not been consistent in the literature. Dixon et al [6] presented a 93% survivorship of the PFC system (DePuy) at 15 years with re-operation for any reason as the endpoint in a single surgeon study assuming that all patients lost to follow-up had a failure of the implant (worst case scenario).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations